Brutes or Angels : Human Possibility in the Age of Biotechnology - Bradley, James T., 1948- (Book collections on Project MUSE., 2013)
"With stem cell research, Dolly the cloned sheep, in vitro fertilization, age retardation, and pharmaceutical mind enhancement, humankind is now faced with decisions that it has never before had to consider. The thoughtfulness, or lack of it, that we bring to those decisions will largely determine the future character of the living world. Brutes or Angels will facilitate informed choice making about the personal use of biotechnologies and the formulation of public policies governing their development and use. Ten biotechnologies that impact humans are considered: stem cell research, embryo selection, human genomics, gene therapies, human reproductive cloning, age retardation, cognition enhancement, the engineering of nonhuman organisms, nanobiology, and synthetic biology. With deft and assured use of metaphors, analogies, diagrams, and photographs, James T. Bradley introduces important biological principles and the basic procedures used in biotechnology. Various ethical issues--personhood, personal identity, privacy, ethnic discrimination, distributive justice, authenticity and human nature, and the significance of mortality in the human life cycle--are presented in a clear and unbiased manner. Personal reflection and group dialogue are encouraged by questions at the end of each chapter, making this book not only a general guide to better informed and nuanced thinking on these complex and challenging topics but also an appropriate text for bioethics courses in university science departments and for adult education classes."--Jacket.